Parental Participation in the Learning Process of Sunday School at Cetya Sangha Ratana Gianyar - Kartini, Ni Ketut; Acep, Lauw; Priyono , Edi (Abrahamic Religions: Jurnal Studi Agama-Agama, 2026)
This research is motivated by the phenomenon of declining participation and attendance rates of children at the Cetya Sangha Ratana Gianyar Buddhist Sunday School (SMB), where the average attendance is only 10–15 children out of 25–30 enrolled. The purpose of this study is to determine the involvement of parents as pubbacariya (first teachers) in supporting the sustainability of children's Dhamma learning through the Cetya Sangha Ratana Gianyar Buddhist Sunday School. This study uses a descriptive phenomenological qualitative approach to explore parents' subjective experiences. Data were collected through in-depth interviews with 7 parents as key informants, as well as observation and documentation. The results show that parents understand the role of pubbacariya as a moral and spiritual responsibility in shaping children's character, but their implementation is still dominated by passive involvement, such as limited to dropping off and picking up children. The main inhibiting factors for active involvement are time constraints due to uncertain work hours and schedule conflicts with socio-religious obligations in the community. The discussion reveals that parental involvement is influenced by the individual's construction of meaning towards Dhamma education and the availability of social support from the family. The study's conclusions confirm that the sustainability of children's Dhamma learning is highly dependent on the synergy between the family and the SMB institution. Strengthening parents' awareness of their spiritual role is key to addressing the decline in children's participation in religious education